2019
DOI: 10.3390/antibiotics8030155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LysBC17, a Lytic Endopeptidase from Bacillus cereus

Abstract: Bacillus cereus, a Gram-positive bacterium, is an agent of food poisoning. B. cereus is closely related to Bacillus anthracis, a deadly pathogen for humans, and Bacillus thuringenesis, an insect pathogen. Due to the growing prevalence of antibiotic resistance in bacteria, alternative antimicrobials are needed. One such alternative is peptidoglycan hydrolase enzymes, which can lyse Gram-positive bacteria when exposed externally. A bioinformatic search for bacteriolytic enzymes led to the discovery of a gene enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…in controlling plant pathogens (26,27). Antagonistic activities of these bacilli take place primarily through the production and secretion of various bioactive secondary metabolites (11,14,(28)(29)(30)(31)(32) and lytic enzymes (33)(34)(35)(36). Verschuere et al (37) argued that among bacteriabased antagonists, B. subtilis is one of the most studied and used bacteria with a wide range of activities against phytopathogens.…”
Section: Bacillus Spp As Antagonists Of Phytopathogensmentioning
confidence: 99%
“…in controlling plant pathogens (26,27). Antagonistic activities of these bacilli take place primarily through the production and secretion of various bioactive secondary metabolites (11,14,(28)(29)(30)(31)(32) and lytic enzymes (33)(34)(35)(36). Verschuere et al (37) argued that among bacteriabased antagonists, B. subtilis is one of the most studied and used bacteria with a wide range of activities against phytopathogens.…”
Section: Bacillus Spp As Antagonists Of Phytopathogensmentioning
confidence: 99%
“…LysBC17, a recombinant endolysin prophage derived from the genome of B. cereus strain Bc17, was reported to have narrow-spectrum lytic activity against several Bacillus strains [ 153 ]. Swift et al reported similar activity in PlyCP10 and PlyCP41 endolysins obtained from the genome of Bacillus bacteria [ 154 ].…”
Section: Newly Prospective Pharmaceutical Candidates To Mitigate Antimicrobial Resistancementioning
confidence: 99%
“…Among the endolysins, muramidase, which is found in the Pseudomonas aeruginosa phage phiKZ gp144 lysin [15], is the rarest type; in contrast, amidases that hydrolyze the most conserved bonds in the peptidoglycan are most widely distributed [16][17][18][19]. Studies of endopeptidases have shown that Listeria endolysin Ply500, Ply118 [20], and some of the Bacillus cereus endolysins [21,22] possess L-alanyl-D-glutamate endopeptidases. Other, staphylococcal endolysin phi11 possess D-alanyl-glycyl endopeptidase and cleave within peptides that cross-link the cell wall [23].…”
Section: Mechanisms Of Action Of Endolysins Against Gram-positive Patmentioning
confidence: 99%